Efektivitas Penggunaan Speechtron A1 Sebagai Media Pengajaran Pengucapan Kata Kerja Reguler Berakhiran –Ed dalam Teks Naratif (Penelitian Eksperimen pada Siswa Kelas X SMA Unggulan Nurul Islami Semarang Tahun Ajaran 2011/2012) - Zuhri, Mohammad Noor; Lizamuddin, Ahmad (Neolectura, 2025)
The study investigates the effectiveness of A1 SpeechTRON as a medium for teaching –ed ending regular verbs to tenth graders at SMA Unggulan Nurul Islami Semarang in the academic year 2010/2011. This study aimed; (1) How the use of A1 SpeechTRON as medium to teach pronunciation of –ed ending regular verbs in the narrative texts at the tenth graders of SMA Unggulan Nurul Islami Semarang in academic year of 2011/2012?, (2) How the effectiveness of A1 SpeechTRON as medium to teach pronunciation of – ed ending regular verbs in the narrative texts at tenth graders of SMA Unggulan Nurul Islami Semarang in academic year of 2011/2012?. The research involved 24 students and was conducted in two groups; an experimental group taught using the software and a control group taught without the software. Data collection involved pre and post-test reading aloud tests, with t-tests used to analyze differences between the two groups. The study found that teachers needed to conduct lessons in language laboratory, provide multiple computers/laptops, and group students into groups to practice using the software. Additionally, the software was CALL-learning-based, allowing students to practice outside of class. The pre-test average for the experimental group was 57.50, while the control group had 58.92. The post-test average was 68.75, and the t-test score was higher than the t-table (1.905 > 1.717). Researcher suggests that A1 SpeechTRON may be an alternative media for teaching –ed ending regular verb pronunciation. The study concludes that A1 SpeechTRON is an effective tool for teaching –ed ending regular verbs in narrative texts.